A study on bacterial dissemination and pathology of experimental intraperitoneal infection of broiler chickens with Pasteurella multocida - Al-Shabibi, Salem A.; Al - Joboury, Khalil H.; Al-Hyali, Harith M. (The Iraqi Journal of Veterinary Medicine, 2003)
Following intraperitoneal inoculcation of 11week - old broiler chicken with 1ml (109cfu/ml) Pasteurella multocida the organisms were disseminated in different organs at specific intervals. The microorganisms presisted in the brain (69.23%) for 19 days postinoculation, in the kidneys and ovary or testis (76.92%) for 23 days, in liver (92.31%), in spleen and lungs (100%) and in heart (84.62%) and for 27 days postinoculation in all of these organs. During the first week postinoculation (acute stage). There were extensive congestion, edema, thrombosis and petichial and eccymotic haemorrhages in the various organs. Infiltration of heterophils, fibrin deposition and acute necrotic areas were also found in different organs such as the brain, meninges, intestine, liver, spleen, kidneys, lungs, heart wall and ovary or testis. During the second week postinoculation (subacute stage), the Infiltration of heterophils, fibrin deposition and necrotic areas in different organs were localized and replaced gradually from the outside by lymphocytes and macrophages to form early pyogranulomas. Also, hyperplasia of peyer's patches and solitary lymphoid nodules in the intestinal wall were predominant. During the 3rd and 4 weeks postinoculation (chronic stage), the early pyogranulomas seen in subacute stage become more localized and chronic, consisting of central areas of necrosis surrounded by lymphocytes, macrophages, and giant cells and on the outside there was fibroblasts proliferation. These chronic granulomas were mostly predominant in liver, lungs, kidney and ovary or testis. Also, lesions of chronic necrotic enteritis were seen in certain cases. The above findings revealed that acute septicemic lesions, followed by pyogranulomas and finally chronic granulomas were persistent lesions associated with Pasteurella multocida infection.